1989
DOI: 10.1016/0014-5793(89)80547-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the monomeric nature of thymosins

Abstract: According to gel‐filtration experiments, α‐ and β‐thymosins appear to form oligomers, which are 4‐5‐fold larger than the corresponding polypeptides. However, on analysis by sedimentation equilibrium ultracentrifugation, prothymosin α and thymosin β4 showed relative molecular masses of 12 800 and 4600, which are close to the values calculated from their amino acid sequences, confirming their existence in solution as discrete monomeric entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
4
11
0
1
Order By: Relevance
“…Human pTK was produced in E. coli and puri¢ed by the hot phenol extraction method developed by Evsta¢eva et al [20], which is based on the unique tendency of pTK to accumulate in an aqueous phase rather than in an organic phase, like all bacterial proteins. The protein was puri¢ed further by anion exchange chromatography to more than 99% purity and showed characteristic features reported previously [7,23,24]. Thus, in the course of gel-¢ltration chromatography, pTK eluted as a protein with an apparent molecular mass of 58.4 þ 0.7 kDa (not shown) ; the molecular mass calculated from its amino acid composition is 12 kDa.…”
Section: Resultssupporting
confidence: 63%
“…Human pTK was produced in E. coli and puri¢ed by the hot phenol extraction method developed by Evsta¢eva et al [20], which is based on the unique tendency of pTK to accumulate in an aqueous phase rather than in an organic phase, like all bacterial proteins. The protein was puri¢ed further by anion exchange chromatography to more than 99% purity and showed characteristic features reported previously [7,23,24]. Thus, in the course of gel-¢ltration chromatography, pTK eluted as a protein with an apparent molecular mass of 58.4 þ 0.7 kDa (not shown) ; the molecular mass calculated from its amino acid composition is 12 kDa.…”
Section: Resultssupporting
confidence: 63%
“…1), both in reducing and non-reducing conditions. This data agrees with the experimental data for gel filtration which we [21] and others [22] have obtained, deducing that ProTa presents a strong aggregating tendency.…”
Section: Labeling Of Prota With "'Isupporting
confidence: 93%
“…It appears surprising that a peptide of only 5 kDa molecular mass does not freely diffuse through nuclear pores. However, structural studies have implicated that thymosin β 4 is an elongated molecule (Zarbock et al, 1990;Czisch et al, 1993;Ballweber et al, 2002) and data from gel filtration experiments have shown that it migrates like a protein of considerably higher molecular mass (Haritos et al, 1989). Future experiments will aim to identify the cytoplasmic factors involved in its nuclear translocation and binding partners.…”
Section: Discussionmentioning
confidence: 99%